The dynamics of the incidence of breast cancer in the Moscow region (2011-2018) - Ekaterina V. Markarova; Lali M. Kogoniya; Vladimir L. Astashov (LLC "MEDIAFORMAT", 2021)
Aim. The purpose of the study was to analyze the incidence of breast cancer (breast cancer) in the Moscow Region (MO) for a period of time from 2015 to 2018. Materials and methods. The data of the territorial Cancer Register of the MO are used. Results. During the observation period of 4 years, 14 024 new cases of breast cancer were diagnosed on the territory of the Moscow Region. Analysis of data on morbidity and mortality from malignant neoplasms is of great importance for determining the needs of the population in specialized medical care.